Integrity, Pride, and Love as Power in Jane Austen’s Novel:“Pride and Prejudice” - Ratna Padmi Trihartanti; Sri Dewiyanti; Muhammad Yazidus Syukri; Siti Yuliah (University of Surakarta, 2023)
This study aims at finding out that variables of relative power (P) are not only social status, age, education and wealth. Another aim is to show that negative politeness strategies do not always belong to someone with higher social power. Relative power is one element of social variables which decides politeness strategies to be employed. Pride and Prejudice reveals that integrity, pride and love are also variables of relative power, and they are also able to prove that though someone’s social status is not high and her social distance with another participant is asymmetric, she could have power over someone else with higher social status. Power characterized with integrity, pride, belief, and freedom from being dominated is called personal power; meanwhile, power which variables determined by good personality, attractive physical appearance, and wit is called referent power. This study uses qualitative method and the data which mostly are refusal taken from Pride and Prejudice. The main character of Pride and Prejudice shows us that integrity, pride, and love could be the variables of power deriving from Personal and Referent power, and those powers could develop and deepen relative power in social variables to be applied in politeness studies.